The exposure of microfinance institutions to financial risk - Thomas Gietzen (Review of Development Finance, 2017)
This study examines the exposure of microfinance institutions to liquidity-, interest rate and foreign exchange (FX) risk. Using manually collected data from microfinance institutions' financial reporting, I find that the microfinance sector faces minimal liquidity risk, high interest rate risk and a lower than commonly assumed exposure to FX risk. Linking risk exposure to institutional characteristics, the data shows that legal status and regional affiliation are correlated with risk exposure while regulatory quality is not. Results suggest that the development community may not expect large benefits from expanding the plethora of current measures taken to mitigate liquidity or FX risk.
Keywords: G21; G32; O16; 650; Microfinance; Financial risk; Liquidity risk; FX risk; Regulation